Analysis of Nurse’s Reflection on Success or Failure of Blood ithdrawal by Vein Types - B. , Hema; V. , Sujatha; Sweenie J, Edna; B. , Madhura Vani; M. , Swarnalatha (International Journal of Psychosocial Rehabilitation, 2020)
We’ll put this information to good use in nursing school. We thus requested 19 clinical nurses to perform a blood withdrawal procedure using four distinct kinds of blood vein simulator models, each with varying degrees of difficulty. In this research, we questioned nurses to learn about their thoughts on the elements that determine whether or not a patient is able to draw blood successfully. In light of the findings, we qualitatively assessed their mental state while using the approach.